On the Nature of Marx's Things : Translation as Necrophilology - Lezra, Jacques, 1960- (Book collections on Project MUSE., 2018)
This work traces to Karl Marx's earliest writings on the Epicurean tradition, a subterranean, Lucretian practice that this text calls 'necrophilological translation'.